MODUL DIGITAL UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS PROSEDUR DAN KEMANDIRIAN BELAJAR SISWA (Digital Module to Improve the Ability Write Procedure Text and Student Self-Regulate Learning) - Wikanengsih Wikanengsih; Muhamad Hatta (SAWERIGADING, 2023)
The objectives of this study (1) produce digital modules using demonstration methods, (2) knowing the response of students and teachers to digital modules, (3) knowing obstacles during development, (4) testing the effectiveness of the use of digital modules using demonstration methods in improving the ability to write procedure texts compared to conventional teaching materials, (5) testing the effectiveness of using digital modules using demonstration methods in increasing students' learning independence compared to conventional teaching materials. The research method used is R D (Research and Development) from Borg and Gall which is simplified into 5 main steps. Data is collected through observation, interviews and questionnaires. Instrument data processing procedures include validity test, normality test, paired sample t test, paired sample statistics test, homogeneity test, independent sample t test, independent static group test sample t test, n-gain test, and descriptive analysis. The research locations are at SMK Texar Karawang, SMK Sehati Karawang, SMK BK 1 Karawang, and SMK PGRI Telagasari. The results of this development research are in the form of digital modules using demonstration methods. The digital module format is generated through google sites.com and question creation through google form.com. The responses of the students and teachers of the four schools were either categorized or agreed. Several obstacles were found during the development of digital modules. The results of the product test proved the effectiveness of the digital module using the demonstration method in improving the ability to write procedure texts and student learning independence in the experimental class compared to conventional teaching materials in the control class. AbstrakTujuan penelitian ini (1) menghasilkan modul digital (2) mengetahui respon siswa dan guru terhadap modul digital, (3) mengetahui kendala saat pengembangan, (4) menguji efektivitas penggunaan modul digital menggunakan metode demonstrasi dalam meningkatkan kemampuan menulis teks prosedur dibandingkan bahan ajar konvensional, (5) menguji efektivitas penggunaan modul digital menggunakan metode demonstrasi dalam meningkatkan kemandirian belajar siswa dibandingkan bahan ajar konvensional. Metode penelitian yang digunakan adalah R D (Research and Development) dari Borg and Gall yang disederhankan menjadi 5 langkah utama. Data dikumpukan melalui observasi, wawancara serta angket. Prosedur pengolahan data instrumen meliputi uji validitas, uji normalitas, uji paired sample t test s, uji paired sample statistics, uji homogenitas, uji independent sample t test, uji grup stastistik independen sample t test, uji n-gain, dan analisis deskriptif. Lokasi penelitian di SMK Texar Karawang, SMK Sehati Karawang, SMK BK 1 Karawang, dan SMK PGRI Telagasari. Hasil penelitian pengembangan ini berupa modul digital menggunakan metode demonstrasi. Format modul digital dihasilkan melalui google sites.com dan pembuatan soal melalui google form.com. Respon siswa dan guru keempat sekolah terkategori baik atau setuju. Ditemukan beberapa kendala saat pengembangan modul digital. Hasil uji produk membuktikan keefektifan modul digital menggunakan metode demonstrasi dalam meningkatkan kemampuan menulis teks prosedur dan kemandirian belajar siswa pada kelas eksperimen dibandingkan bahan ajar konvensional pada kelas kontrol.